The Relationship Between Knowledge and Attitudes of Women of Childbearing Age (WUS) and Early Detection of Cervical Cancer Using the Visual Inspection with Acetic Acid (VIA) Method - Ririn Widyastuti; Martina Fenansia Diaz (Journal of Tropical Diseases and Health Science, 2024)
Cervical cancer is a type of cancer that occurs in the cervix or the neck of the uterus. Cervical cancer remains a major cause of morbidity and mortality among women globally and is a gynecological disease with a relatively high malignancy rate. The low level of knowledge among women of reproductive age (WRA) regarding the importance of early detection of cervical cancer in Indonesia is due to a lack of awareness and information about methods for prevention and early detection of cervical cancer. Visual Inspection with Acetic Acid (VIA) is one method for the early detection of cervical cancer. The purpose of this study was to determine the relationship between the knowledge and attitude of women of reproductive age (WRA) and the early detection of cervical cancer using the VIA method at Bakunase Community Health Center in 2016. This study used an analytical survey research design with a cross-sectional approach. The population in this study was WRA, totaling 622 people. The sampling technique used was accidental sampling, which involved 86 people. The data collection instrument was a questionnaire. Data analysis included univariate analysis in the form of frequency distribution and percentage, and bivariate analysis using the chi-square (x2) test. Out of the 86 respondents, 47 respondents (54.7%) had good knowledge and 39 respondents (45.3%) had poor knowledge. Regarding attitude, there were 65 respondents (75.6%) with a positive attitude and 21 respondents (24.4%) with a negative attitude. There is a relationship between the knowledge and attitude of WRA and the early detection of cervical cancer using the VIA method with a p-value of 0.043.